RESEARCH ON THE COMMERCIAL INFLUENCE OF SOCIAL CURRENCY ON PERCEIVED QUALITY - Lin , Peiyu (Journal of Buddhist Education and Research (JBER), 2024)
The electronic age has transformed consumers into knowledge disseminators. Instagram provides a good platform for consumers, and the interaction between consumers has become a new channel for receiving business information. Sharing and disseminating a large amount of information on online social platforms has made the way to measure brand must change. How consumers comment on brands has become much more important than the active communication of brands in the past. This study uses the framework of Internet generation brand measurement - "Social Currency", which is further divided into social interaction and social benefits. This study incorporates these dimensions into the discussion to understand the degree of correlation. Discuss the influence of the term social currency, which is derived from the interaction of consumers through the online community, on the perceived quality. The perceived quality is divided into two aspects: product quality and service quality and discusses "electronic word-of-mouth" from a business perspective. The influence of "brand trust" on "product quality" and "service quality". The research results show that different levels of interaction in the social currency will affect different levels of relationships. The higher the level of interaction, in addition to gaining benefits, it can further affect the formation of higherlevel relationships such as a sense of belonging and identity. In addition, electronic word-ofmouth will positively affect product quality and service quality through brand trust, and it is explained that consumers on online community platforms have a greater impact on perceived service quality than perceived product quality.